From Pixels to Patterns: A Review of Land Cover Analysis Techniques - Surana, Priya; Phulpagar , Bhagwan; Patil , Pramod D. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Land cover analysis is a crucial task in environmental studies and management. In recent years, deep learning methods have been increasingly applied to land cover analysis, showing promising results. In this literature review, we compare the performance of various land cover analysis studies using different datasets and deep learning methodologies. Our analysis shows that deep learning approaches have outperformed traditional methods in terms of overall accuracy. We found that studies using Sentinel-2 and Landsat 8 datasets produced the highest accuracies, with some studies achieving up to 97.8% accuracy. Deep learning-based methods such as deep belief networks, support vector machines, random forests, and deep neural networks have been used to classify land cover with high accuracy. These findings suggest that deep learning approaches are a powerful tool for land cover analysis and can provide valuable insights for environmental management and policy. Introduction: Land cover analysis is an important aspect of natural resource management and has become increasingly important in recent years due to the need for accurate and timely information on land use changes. Land cover analysis is a crucial task in environmental monitoring and management.Various techniques have been developed to analyze land cover, including remote sensing, GIS, and machine learning. land cover analysis has been increasingly performed using deep learning techniques due to their high accuracy and efficiency and to summarize the current state of research on this topic. The accuracy of these techniques is critical to ensure the effectiveness of land use management strategies. This literature review paper aims to compare the accuracy of different land cover analysis techniques and summarize the current state of research on this topic.